The Effect of Using the Demonstration Method on Students' Skills in Practicing Wudhu - Aisah, Ai (Interdisciplinary Social Studies, 2021)
The material for Wudhu practice is not possible only with the lecture method for it causes students lack of understanding of the material. By using the demonstration method, students are expected to be able to practice Wudhu correctly. The condition of the second-grade students of DTA Al-Fauzaniyyah Solokan Jeruk Sub-District still incorrectly practice Wudhu. To discover the process of applying the demonstration method to learning Wudhu material for class II students of DTA Al-Fauzaniyyah in Solokan Jeruk Sub-District, the skills of the students in practicing Wudhu before and after the use of the demonstration method, and whether there was an effect of the demonstration method on students' skills in practicing Wudhu. This study uses descriptive quantitative research on 28 second-grade students of DTA Al-Fauzaniyyah. This research uses interview and test method. Based on the research, the use of the demonstration method in learning Wudhu material is considered very appropriate since can provide a direct learning experience to students. The analysis used is descriptive analysis. The results of this study indicate that the value of tcount = 13.21 > ttable = 2.052 at the 5% confidence level. Thus, H0 is rejected and Ha is accepted. Hence, the results of the study prove that there is an effect of using the demonstration method on students' skills in practicing Wudhu.